2021
DOI: 10.3389/fcvm.2021.730155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Therapy on Anxiety and Depression in Patients With Coronary Heart Disease: A Meta-Analysis of a Randomized Controlled Study

Abstract: Objective: The purpose of this review was to evaluate the effect of exercise therapy on anxiety and depression symptoms in patients with coronary heart disease (CHD).Methods: A systematic review of papers published between January 2000 and February 2021 was conducted. MEDLINE, Embase, the Cochrane Library and Web of Science were searched. Meta-analysis was used to compare the results of the included studies. Bias risk assessment was performed using the Cochrane Collaboration bias risk tool. If half or more of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Participants reported psychological benefits that included decreased anxiety and stress, increased resilience, motivation to exercise, alertness, and positive mood. Our findings mirror and potentially provide important qualitative context to quantitative studies that show significant improvements in anxiety and depression among patients with CVD completing exercise-based CR 52–54. Some studies have suggested a bidirectional relationship between depression and cardiovascular health 55,56.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Participants reported psychological benefits that included decreased anxiety and stress, increased resilience, motivation to exercise, alertness, and positive mood. Our findings mirror and potentially provide important qualitative context to quantitative studies that show significant improvements in anxiety and depression among patients with CVD completing exercise-based CR 52–54. Some studies have suggested a bidirectional relationship between depression and cardiovascular health 55,56.…”
Section: Discussionsupporting
confidence: 73%
“…Our findings mirror and potentially provide important qualitative context to quantitative studies that show significant improvements in anxiety and depression among patients with CVD completing exercise-based CR. [52][53][54] Some studies have suggested a bidirectional relationship between depression and cardiovascular health. 55,56 These pathophysiological pathways are not fully understood and require additional examination.…”
Section: Exercise Benefitsmentioning
confidence: 99%
“…It is difficult to avoid heterogeneity due to the difference in exercise modalities as well as the duration and frequency of exercise adopted in the studies. In addition, the total exercise duration was more comparable between groups, as compared with other meta-analyses 10 that indicated the frequency of exercise only. The benefits from different exercise modalities may vary greatly, which might have also affected the results of our subgroup analysis.…”
Section: Discussionmentioning
confidence: 57%
“…Recent studies evaluated the effects of CR on the physical performance and psychological status after revascularization (including PCI and CABG) for CAD, which showed that CR after revascularization could alleviate anxiety and depressive symptoms, improve physical performance, and reduce the recurrence of myocardial infarction and cardiac mortality. 10 , 11 , 12 However, to the best of our knowledge, there has been no meta-analysis exploring the effect of CR on the cardiopulmonary function after CABG. Therefore, this systematic review and meta-analysis aimed to analyze the effect of CR on the cardiopulmonary function of patients with CAD after CABG and to assess whether CR could improve the postoperative cardiopulmonary function in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity is defined as any bodily movement produced by skeletal muscles that require energy expenditure [ 15 ] and is related to different health benefits: better weight control [ 16 , 17 ], glycemic control [ 18 , 19 ], pain management [ 20 , 21 ], and psychiatric symptomatology [ 21 , 22 , 23 , 24 ], as well as lower risk of certain types of cancer [ 25 ], among others. It is therefore conclusive that exercise promotes better health-related quality of life [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%